Contact Investigation and Preventive Therapy as Tuberculosis prevention in Children with Tuberculosis Household Contact: A Systematic Review - Apriana Rahmawati; Budi Utomo; Makhfudli Makhfudli (Jurnal Ners, 2020)
Introduction: The increasing tuberculosis cases in children showed management of Tuberculosis itself.  There was a finding of TB case in children according to WHO TB report 2019 that not all childrens being well diagnosed, treated or reported each year. This systematic review aims to describes implementation of TB prevention often missed in children with adult TB household contacts.Method: This study uses based on PICO, which contains Participants are family who living household with adult TB, Interventions are CI followed by PT, no comparison, Outcomes are improving the implementation of CI and PT. Searching for article is using the Scopus, PubMed, and Science Direct and found 15 articles in final which limited to the last 3 years (2017-2020). Keywords used in searching are” Tuberculosis”, “Transmission”, and “Preventive Therapy”. The population included were respondents identified as family having child aged ≤ 15 years with TB Household Contacts. The study design varied in rigorousness form of quantitative and mixed studies.Result: Household Contact (HHC) contribute to TB cases in children.Conclusion: Contact Investigation (CI) and Preventive Therapy (PT) could be succesfull strategies to prevent TB transmission to children provided not only by Health Care Workers (HCWs) but also public concerned to community-based approach in order to encouraged family members of TB affected